The World that Latin America Created. Libro de Margarita Fajardo - Caravaca, Jimena (El Colegio de México, 2023)
Through the institutional analysis of the Economic Commission for Latin America (ECLAC) and the study of the economic ideas proposed by a group of economists whom she calls cepalinos, Margarita Fajardo makes a contribution both to the history of economic ideas and to the ECLAC institutional history. Although it is not central to the work, the research also results in a contribution to the cultural history of the Cold War in Latin America. Keywords: ECLAC. Latin America. Development. Raúl Prebisch.